The Evaluation of the “Guest Teachers” Program: CIPP Model Approach for Academic Year 2024/2025 - Partikasari, Rika; Hamzah, Syukri; Yanti, Fitri April; Wardana, Rendy Wikrama (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The Guest Teachers Program is designed to invite students' parents to serve as one-day guest teachers, inspiring students through various professions while fostering a sense of pride and respect for their parents. This study aims to evaluate the success level of the educational program through an evaluation of the Guest Teachers Program implemented at Kiddie Land Kindergarten, Bengkulu City. The research method employed is descriptive evaluative research, which aims to provide an overview of the program under evaluation. The data analysis technique used in this study is descriptive analysis. The evaluation model applied is the CIPP model (Context, Input, Process, and Product). The CIPP model is designed to evaluate programs comprehensively to make systematic decisions. Based on the conducted research, it can be concluded that implementing the Guest Teachers Program, viewed from context, input, process, and product, is reasonably effective at Kiddie Land Kindergarten, Bengkulu City. This is because the content and objectives of the Guest Teachers Program align well with the school's needs.